Lived experiences of mothers of children who have experienced/perpetrated sibling sexual abuse - Kelani, S.K (2019)
The majority of research regarding sibling sexual abuse has focused on victim and perpetrator experiences and there has been less attention paid toward exploring the experiences of mothers, although they are considered responsible for supporting the child after disclosure. The current study aims to fill the gap by analysing mothers experiences regarding the disclosure of SSA. This research uses Interpretative Phenomenological analysis to explore lived experiences of mothers of children who have perpetrated/experienced sibling sexual abuse. The research aimed to explore how mothers understand it, manage it, feel about it, and have reacted to it. Interviews were conducted with 4 mothers, aged between 37-45 years and all from the Midlands UK. Five themes were identified in the analysis; rollercoasters, torn loyalties, power, managing knock-on-effects and rewriting the future. The main conclusions drawn from this research were the difficulties mothers face in sibling sexual abuse cases because they care for both the perpetrator and victim and want to meet the needs of both, since they are both their children. Furthermore, the research found that mothers felt their future had to be altered to include the impact of the abuse which occurred within the family, and the changed family circumstances. Moreover the research demonstrated that mothers went through an on-going process which involved them feeling a mixture of intense emotions once they discovered the abuse of their child.